The Co-Evolution of Markets and Regulation in the Japanese Functional Food Industry: Balancing Risk and Benefit - Keigo Sato; Kota Kodama; Shintaro Sengoku (Foods)
Amid the global rise in chronic diseases and escalating costs, functional foods have become a preventive solution, offering benefits beyond essential nutrition. However, the regulatory landscape remains complex, requiring a balance between consumer protection and industry innovation. Previous studies seldom examine how markets and regulation evolve, leaving a clear gap that this review addresses. This study aims to propose a framework focusing on the risk side (quality and safety) and benefit side (functionality) to analyze functional food regulations, and to examine the evolution of regulatory systems and their impact on industry development through a historical analysis of Japan’s functional food regulation from the 1960s. The results reveal that regulations have co-evolved with industry growth, dynamically balancing the risk and benefit sides. Milestones, such as the introduction of the Foods with Function Claims (FFC) system and the Beni-koji (red yeast rice) contamination incident in 2024, highlight adjustments in this balance. The findings suggest that the risk-/benefit-side framework provides a valuable lens for understanding the interplay between regulation and innovation in the functional food industry. This study contributes to regulatory science by offering empirical evidence from the sector and has practical implications for policymakers seeking to design frameworks that promote both innovation and consumer welfare.